Amputation of uterine corpus as the intraoperative modification during cesarean radical hysterectomy for invasive cervical cancer during pregnancy - Matsuo, Koji; Enomoto, Takayuki; Yamasaki, Masato (International journal of clinical oncology, 2010)
Objective Cesarean radical hysterectomy (CRH) for invasive cervical cancer during pregnancy is characterized by heavy blood loss. Any surgical modifications made in an attempt to reduce the blood loss are valuable. Our study was designed to evaluate the efficacy of amputating the uterine corpus during CRH. Methods All cases of radical hysterectomy (RH) were evaluated. Cases were divided into: (a) cesarean section immediately followed by RH for invasive cervical cancer complicating pregnancy (CRH group); and (b) RH for nonpregnant subjects (RH group). The information abstracted included estimated blood loss (EBL), operative time, intraoperative transfusion, and use of amputation of uterine corpus during CRH. Nonparametric tests were used for the statistical analysis. Results There were five CRH cases (3 for CRH with amputation, 2 for CRH without amputation) and 209 RH cases were evaluated for statistics during the study period. The difference in mean operative time between the CRH group and the RH group was not statistically significant: 276.6 min (range 160–425) versus 297.3 min (range 147–645), p = 0.66. The mean EBL for the CRH group was significantly larger than that for the RH group: 2106.6 ml (range 730–4150) versus 858.8 ml (range 150–4770), p < 0.001. Mean operative time and mean EBL for CRH with amputation of uterine corpus were significantly less than those for CRH without amputation of uterine corpus: operative time, 186.0 min (range 160–228) versus 412.5 min (range 400–425), p = 0.043; EBL, 1034.3 ml (range 730–1540) versus 3715.0 ml (range 3280–4150), p = 0.043. No intraoperative tumor exposures were observed in the amputated cases. Conclusion Amputation of uterine corpus during CRH for invasive cervical cancer during pregnancy significantly improves the intraoperative performance, although it should be used with care.